“A coleta que transforma”: uma etnografia dos beneficiamentos de resíduos recicláveis na Associação dos Catadores de Papel, Papelão e Materiais Recicláveis (ACREPOM), de Araçatuba/SP - Bonifácio, André Luiz Alves (2020)
In Brazil, the collection and collection of recyclable materials occurs mostly through the action of collectors and recyclers. Often occupying a precarious role in the workforce under capitalism, the participation of this front line in the recycling process created the need to organize themselves in order to provide an effective management of solid waste in cities. The large amount of waste generated and discarded, linked to the current economic model, disregards many of the social asymmetries that develop within the relationships of those who work with disposal; naturalizes cultural issues that go through not only the disposal of garbage and / or waste, but also the subjects who operate in this process; and the perceived ecological quality is alien to it, becoming one of the great challenges of contemporary times. The methodology used in this work seeks to understand the transformational relationships between waste pickers and recyclers and the donation of recyclable waste through ethnographic field research, accompanied by documentary analysis on the association called ACREPOM and an interpretation in the light of data construction in the face of context of dynamics that permeate micro work relations with the materiality of residual objects, with the dominant macro situations of society, history and culture, as well as their values. In addition to having fragments of the interviews and participant observation, which are present throughout the text with other research techniques suitable to current ethnography, the theory of value in Karl Marx supported much of the critical reflection on the data constructed and interpreted. The data obtained by anthropological bias, allow the understanding of the relationships between subjects and objects, humans and waste, within the concepts of development, sustainability and associativism, pointing out the intimate relationship between collectors / recyclers and recyclable materials. Understanding a dialectical vision between production-consumption-disposal, ACREPOM's creation and organization processes are highlighted, as well as its challenges for its maintenance and strengthening. I understand the need for this category to be more and more organized, in order to effectively manage urban solid waste and political-economic confrontations